Tapping All Resources for Recovery and Disaster Funding. Issue 1 (1st January 2013) - Spence, Shannon; Goldbloom‐Helzner, David; Weisman, Richard; Keane, Patricia
Abstract : Drinking water and wastewater utilities in the United States have experienced various types of disasters, including floods, tornadoes, wildfires, hurricanes, and earthquakes. Major disasters can disrupt water/wastewater operations and cause significant damage, such as flooding of treatment facilities, destruction of water towers, loss of critical power supply, inoperable pump stations, and multiple breaks in water mains. The costs to respond after an incident can be overwhelming, and it takes days, weeks, months, or years to recover.